Health Impact Assessment as a tool in India for evaluating how policies, programs influence the health of the population - Nitesh Kumar; Sanjeev Kumar Rasania (Indian Journal of Community Health, 2024)
Health Impact Assessment (HIA) systematically assesses the health impacts of policies, programs on a population, with a focus on the holistic well-being of individuals. This approach employs diverse methods to identify positive and negative health impacts, along with unintended consequences, offering recommendations for effective management. HIA considers economic, social, psychological, environmental, and organizational factors in community health. The process involves key steps like assessing baseline health, identifying impacts, quantifying and valuing them, ranking importance, and proposing management recommendations. HIA can be prospective, retrospective, or concurrent during implementation.
Keywords: Health Impact Assessment; Health determinants; India